Function theory: mathematics and economics - Mejía M., Luis (2014)
In the daily life constant situations arise in which two or more magnitudes relate between yes by means of some rule. It is there where, without realizing, the functions are proposed, and the most surprising thing is that still without knowing them formally we are using them!.To admit that in certain situation a function is imprisoned yes and to be able to establish an economic model who represents her is of great usefulness since with an equation we can realize an analysis of the situation and do predictions.